Optimalisasi Perlindungan Hukum bagi Whistleblower dalam Tindak Pidana Korupsi di Indonesia: Analisis Kelemahan Regulasi dan Implikasi Praktis - Amelia, Husna; Mulyana, Aji; Amalia, Mia (Journal of Contemporary Law Studies, 2025)
This research aims to analyze the regulatory weaknesses and practical implications of legal protection for whistleblowers in Indonesian corruption cases. Its primary focus is to evaluate the effectiveness of the existing legal framework, particularly concerning overlapping authority among state institutions. Using a juridical-empirical (socio-legal) approach, this study combines a normative legal analysis of statutes with an in-depth case study of 47 corruption reports filed between 2018 and 2023 to assess its practical implementation. The findings reveal that legal protection remains highly inadequate. Regulatory overlaps between the Witness and Victim Protection Law (UU PSK), the KPK Law, and Supreme Court Regulation No. 4 of 2011 create legal uncertainty and institutional confusion. Empirically, 68% of whistleblowers in the analyzed cases faced retaliation, ranging from intimidation to criminalization, which directly deters public reporting. This study concludes that piecemeal reforms are insufficient. A comprehensive overhaul is required, structured around a three-dimensional model: integrated regulatory reform, strengthening the institutional capacity of the Witness and Victim Protection Agency (LPSK) as the central pillar of protection, and transforming the legal culture. A hybrid approach combining full protection with reasonable incentives is recommended to foster a safe ecosystem and encourage public participation in combating corruption.